Morphological Properties of Siloxane-Hydrogel Contact Lens Surfaces. (3rd April 2017) - Stach, Sebastian; Ţălu, Ştefan; Trabattoni, Silvia; Tavazzi, Silvia; Głuchaczka, Alicja; Siek, Patrycja; Zając, Joanna; Giovanzana, Stefano
ABSTRACT: Purpose : The aim of this study was to quantitatively characterize the micromorphology of contact lens (CL) surfaces using atomic force microscopy (AFM) and multifractal analysis. Materials and Methods : AFM and multifractal analysis were used to characterize the topography of new and worn siloxane-hydrogel CLs made of Filcon V (I FDA group). CL surface roughness was studied by AFM in intermittent-contact mode, in air, on square areas of 25 and 100 μm 2, by using a Nanoscope V MultiMode (Bruker). Detailed surface characterization of the surface topography was obtained using statistical parameters of 3-D (three-dimensional) surface roughness, in accordance with ISO 25178-2: 2012. Results : Before wear, the surface was found to be characterized by out-of-plane and sharp structures, whilst after a wear of 8 h, two typical morphologies were observed. One morphology (sharp type) has a similar aspect as the unworn CLs and the other morphology (smooth type) is characterized by troughs and bumpy structures. The analysis of the AFM images revealed a multifractal geometry. The generalized dimension Dq and the singularity spectrum f(α) provided quantitative values that characterize the local scale properties of CL surface geometry at nanometer scale. Conclusions : Surface statistical parameters deduced by multifractal analysis can be used to assess the CL micromorphology and can be used by manufacturers in developing CLs with improved surface characteristics. These parameters can also be used in understanding the tribological interactions of the back surface of the CL with the corneal surface and the front surface of the CL with the under-surface of the eyelid (friction, wear, and micro-elastohydrodynamic lubrication at a nanometer scale).